2010
DOI: 10.1002/cncr.25062
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of radiotherapy for painful bone metastases during the last 12 weeks of life

Abstract: for the Dutch Bone Metastasis Study Group BACKGROUND: Radiotherapy is an effective treatment for painful bone metastases. Whether this applies also in patients with limited survival remains to be investigated. This study analyzed the effect of radiotherapy for painful bone metastases in patients with a survival 12 weeks. METHODS: In the Dutch Bone Metastasis Study, 1157 patients with painful bone metastases were randomized to single fraction (1 Â 8 grays [Gy]) or multiple fraction (6 Â 4 Gy) radiotherapy. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 32 publications
1
47
0
2
Order By: Relevance
“…Multiple imputation was carried out to impute missing values for performance status (n ¼ 14) and the initial response (n ¼ 1). The number of events limited the number of possible covariates, therefore only covariates considered most relevant were included [6,11,15,16], i.e. tumour type (breast versus other), localisation (limb versus other), performance status (World Health Organization 1 or !2), initial response (recurrence after response versus no/insufficient response) and previous (<1 year) or current use of systemic therapy (yes/no).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple imputation was carried out to impute missing values for performance status (n ¼ 14) and the initial response (n ¼ 1). The number of events limited the number of possible covariates, therefore only covariates considered most relevant were included [6,11,15,16], i.e. tumour type (breast versus other), localisation (limb versus other), performance status (World Health Organization 1 or !2), initial response (recurrence after response versus no/insufficient response) and previous (<1 year) or current use of systemic therapy (yes/no).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, patients with a very poor performance status at the BT, have a low probability of improving their performance status because many factors contribute to this status. However, one study showed that such patients with a short life expectancy may benefit from analgesic irradiation [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Bone pain is a common event in patients with skeletal metastases, leading to immobility and decreased quality of life in cancer patients. In addition to pain medication, palliative radiotherapy is the standard of care for patients with uncomplicated localized metastatic bone pain [ 27 ] . Palliative radiotherapy is effective in around 60–70% of patients, and only around 30% of responding patients are totally pain free [ 28 ] .…”
Section: Mr-hifu For Bone Metastasesmentioning
confidence: 99%